Implementation of Tri Hita Karana Teaching to Form Students Characters Quality - I Wayan Mandra; Dhammananda (Jurnal Penjaminan Mutu, 2020)
Tri Hita Karana at the elementary school environment is an effort in learning Hinduism to develop three aspects, namely cognitive, affective and psychomotor. Through religious education, Hindu Religion students are guided to always foster harmonious relations with God, others and the environment. Tri Hita Karana's teachings will be realized through balance in their implementation to maintain a harmonious relationship between humans and God, humans with each other, and humans with the natural environment. From preliminary observations, there are several types of violations or deviations of student behavior that are negative, including the behavior of students who are less obedient to the teacher, rebel or against the teacher's advice, students who are always joking when carrying out tri-sandya, some students who are less active in community service activities and have more chat or stay away when friends work together to clean up the school environment, and some students who seem to prefer littering in the classroom or the schoolyard.